E-Commerce as an Innovation in Social Enterprise Digitalization - S. K, Ernawati (PINISI Discretion Review, 2025)
Digital transformation has opened up new opportunities for the development of social entrepreneurship in Indonesia, particularly through the strategic use of e-commerce as both a distribution channel and a medium for conveying social values. This article aims to analyze how social enterprises utilize e-commerce to integrate economic and social objectives sustainably. The method used is a literature review with a descriptive-qualitative approach, focusing on academic publications from 2019 onwards. The findings show that digitalization allows social enterprises to expand market reach, build strong social narratives, and strengthen collaborative business models. However, challenges such as digital literacy gaps, platform dependency, and unequal access to technology remain significant obstacles. Therefore, synergy among government, academia, and civil society is necessary to create a digital ecosystem that is inclusive and equitable for social enterprises. Digitalization is not merely an economic growth tool but also a space for value-based struggle in constructing a humane and just economic model.